"My Whole Life is Ethics!" Ordinary Ethics and Gene Therapy Clinical Trials. Issue 7 (3rd October 2017) - Addison, Courtney; Lassen, Jesper
ABSTRACT: What and where is ethics in gene therapy? Historical debates have identified a set of ethical issues with the field, and current regulatory systems presume a discrete ethics that can be achieved or protected. Resisting attempts at demarcation or resolution, we use the notions of "ordinary" or "everyday" ethics to develop a better understanding of the complexities of experimental gene therapy for patients, families, and practitioners and create richer imaginings of ethics in the gene therapy sphere. Drawing on ethnographic research in several clinical trials, we show that patients/parents can acquire some control in difficult medical situations, and practitioners can attune their care to their patients' needs. The human provenance of gene therapy practice, and the irreducible sociality of ethics, means that understanding the ethics of this medical field also requires understanding the everyday worlds and relationships of those at its heart.